Atresia of Cavity Follicles in Karakul Sheep in Ontogenesis - Nurmukhamedov, B. M.; Bakhriddinov, K. S.; Davlatov, K. M.; Khudoyqulov, I. A.; Suyunov, Sh. A. (American Journal of Bioscience and Clinical Integrity, 2025)
The article presents the results of studies is given and studied characteristic ovo-follicle and lutiogeny ovarian function seep, and set to seasons and whatever the state of the formation of primordial sexual function, secondary and tertiary follicles with the restoration of reproductive function.